2006
DOI: 10.1242/jcs.03009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of disease-causing lamin A mutants impairs the formation of DNA repair foci

Abstract: Lamins are nuclear proteins that are components of a fibrous network underlying the inner nuclear membrane termed the nuclear lamina, and are also distributed throughout the interior of the nucleus (reviewed by Goldman et al., 2002). Lamins have been classified into two types based on biochemical properties and expression patterns. B-type lamins are expressed in most cells and are encoded by two separate genes, B1 and B2, whereas the A-type lamins have been detected primarily in differentiated cell types. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 67 publications
11
98
1
1
Order By: Relevance
“…This suggests that expression of lamin A mutants affect γ-H2AX redistribution into the nucleus in the presence of DNA damage. This result is in agreement with data described by Manju and coworkers, 30 who observed that cells expressing LMNA mutations causing progeria syndromes (Del50, R471C, R527C and L530P), form a lower percentage of γ-H2AX foci in response to mild doses of cisplatin or UV irradiation, in contrast to cells expressing wild-type GFP-lamin A or the LMNA disease-causing mutations H222P and R482L. Interestingly, a significant higher level of residual damage was observed in irradiated-MADA cells after 24 h from IR.…”
Section: Discussionsupporting
confidence: 94%
“…This suggests that expression of lamin A mutants affect γ-H2AX redistribution into the nucleus in the presence of DNA damage. This result is in agreement with data described by Manju and coworkers, 30 who observed that cells expressing LMNA mutations causing progeria syndromes (Del50, R471C, R527C and L530P), form a lower percentage of γ-H2AX foci in response to mild doses of cisplatin or UV irradiation, in contrast to cells expressing wild-type GFP-lamin A or the LMNA disease-causing mutations H222P and R482L. Interestingly, a significant higher level of residual damage was observed in irradiated-MADA cells after 24 h from IR.…”
Section: Discussionsupporting
confidence: 94%
“…1A, B). However, GFP-tagged lamin mutant Q294P was distributed in aggregates throughout the nucleus, and its expression resulted in aberrant nuclear morphology and disruption of the endogenous lamin A network, consistent with our earlier observation in other cell types (Manju et al, 2006). Importantly, we made the novel observation that endogenous lamin B1 was depleted in 88% of cells expressing lamin A mutant Q294P compared to <5% of cells expressing wild-type lamin A (Fig.…”
Section: Localization Of Gfp-tagged Laminssupporting
confidence: 90%
“…Cells were transfected with a green fluorescent protein (GFP)-tagged lamin A construct by electroporation and maintained in the medium for 24 h. The two constructs that were used were wild-type lamin A and Q294P lamin mutant that causes EMD and have been described earlier (Manju et al, 2006). GFPexpressing cells were sorted in a fluorescence activated cell sorter (FACS) in order to obtain >99% cells expressing the GFP-tagged lamin.…”
Section: Cell Culture Dna Transfection and Cell Sortingmentioning
confidence: 99%
“…GFP-BAF, 17 full-length FLAG-tagged rat prelamin A (LA-WT, pCI mammalian expression vector) and the mutated constructs LA-C661M, LA-L647R and LA-∆50 were transiently transfected into HEK293 cells using FuGene reagent (Roche). 9,12,23,44 Biochemical and immunofluorescence analyses were performed 24 hours after transfection. In human skin fibroblast cells the accumulation of different prelamin A intermediates were obtained using 25 µM mevinolin (Sigma), 10,12 or 20 µM 1-N-acetyl-S-farnesyl-Lcysteine methylester (AFCMe, Alexis).…”
Section: Methodsmentioning
confidence: 99%